EFL (ENGLISH AS A FOREIGN LANGUAGE) STUDENTS’ PERCEPTION ABOUT THE EFFECTIVENESS OF LEARNING READING BY USING ELECTRONIC BOOKS - Septi Merentika Arianda; Aswadi Jaya; Ana Theriana (Esteem Journal of English Education Study Programme, 2023)
The aims of this research was to determine students' perceptions of the effectiveness of learning reading by using electronic books (E-books). The formulation of the problem in this research is focused on what is the students' perception about the effectiveness learning reading by using electronic books (E-books). This research used descriptive qualitative method. The data were collected by triangulation, namely observation, questionnaires, interviews, and documentation. The results of the data showed that students' perceptions about the effectiveness of learning reading by using electronic books (E-books) provide a good perception. Electronic books (E-books) are good learning media to be applied to students to help students learn to be more independent.